2022
DOI: 10.3389/fmed.2021.703661
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Severity in COVID-19 Patients on ACEIs and ARBs—A Systematic Review, Meta-Analysis, and Meta-Regression Analysis

Abstract: Purpose: The primary objective of this systematic review is to assess association of mortality in COVID-19 patients on Angiotensin-converting-enzyme inhibitors (ACEIs) and Angiotensin-II receptor blockers (ARBs). A secondary objective is to assess associations with higher severity of the disease in COVID-19 patients.Materials and Methods: We searched multiple COVID-19 databases (WHO, CDC, LIT-COVID) for longitudinal studies globally reporting mortality and severity published before January 18th, 2021. Meta-ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 103 publications
2
18
0
Order By: Relevance
“…Our results are in the line with the results of multiple published studies that reported that the use of RAAS inhibitors is not associated with increased short-term mortality in COVID-19 patients [17,18]. Our results that suggested a protective effect of ACEIs and ARBs are also consistent with the results of a growing number of studies that associated their use in COVID-19 patients a lower risk of mortality [19][20][21][22].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in the line with the results of multiple published studies that reported that the use of RAAS inhibitors is not associated with increased short-term mortality in COVID-19 patients [17,18]. Our results that suggested a protective effect of ACEIs and ARBs are also consistent with the results of a growing number of studies that associated their use in COVID-19 patients a lower risk of mortality [19][20][21][22].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are generally consistent with previous meta-analyses [42] , [43] , [44] , [45] , [46] of observational studies that the use of ACEIs/ARBs appears to have no significant effect on mortality or disease severity in patients with COVID-19. However, because a substantial proportion of the trials included in previous meta-analyses did not match for confounders, the crude OR may not accurately reflect the association between the use of RAAS inhibitors and COVID-19 clinical outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…As of 28 December 2021 the Covid-19 pandemic has affected >281 million individuals and has led to >5.4 million global deaths (5). Even though many treatments have been proposed to combat COVID-19, there is currently no uniformly successful therapy (6)(7)(8)(9)(10)(11). Although it is a widespread disease affecting multiple systems, obesity has been identified as one of the major comorbid factors in patients suffering from COVID-19 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%